GENDER ISSUE OF THE SOVIET CULTURE AND EDUCATION POLICY IN UKRAINIAN WESTERN REGIONS (DURING 1944-1953) - DURDAS, Halyna (HUMANITARIAN STUDIES: HISTORY AND PEDAGOGY, 2023)
Summary. The article focuses on the gender aspect of cultural and educational policy in Ukrainian western regions during post-war period. Forms and methods of the accelerated Sovietization in these regions are investigated. It’s been clarified that women were actively engaged in urgent tasks implementation of the soviet system in the sphere of culture and education of the west Ukrainian area. In this way soviet government desperately tried to create illusion of active participation of locals in the Sovietization process. The activity of women’s societies especially women’s committees and theme groups which were subordinated by them is explored. It’s identified that being under strict control of the local authorities they decided many problems in culture and education field, though they had only nominal status of public organization under real conditions of Stalin totalitarian system. Motives of the personnel policy of the soviet government in the human resources complication of culture and education institutions during reconstruction period are clarified. Quantity and quality women’s markers involved in culture and education sphere and in particular those who held managing posts are represented. Difficulties occurred with local women during staff complication carried out by the soviet government during the first post-war years are described. Main forms of ideological effect on the women and new arrivals activity are characterized. Mobilization practices used by the soviet government showed that women especially teachers served as a perfect tool of the soviet propaganda. It’s been investigated that special attention was paid to eliminating illiteracy among the adults and women as well. The level of women’s literacy is shown. The process of educational institutions for the illiteral establishment is investigated and their material and personnel providing are characterized. Special attention is paid to the formation of the typical soviet system of the cultural and educational sphere, that becomes political and ideological means of the influence on the local population. It’s stated that women involved into the process of the education and culture Sovietization of the western Ukrainian regions were used by the authorities as means of fighting against Ukrainian national liberation movement.